2010
DOI: 10.1002/pmic.200900768
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression profiles distinguish between experimental invasive pulmonary aspergillosis and Pseudomonas pneumonia

Abstract: We hypothesized that invasive pulmonary aspergillosis (IPA) may generate a distinctive proteomic signature in plasma and bronchoalveolar lavage (BAL). Proteins in plasma and BAL from two neutropenic rabbit models of IPA and Pseudomonas pneumonia were analyzed by SELDI-TOF MS. Hierarchical clustering analysis of plasma time course spectra demonstrated two clusters of peaks that were differentially regulated between IPA and Pseudomonas pneumonia (57 and 34 peaks, respectively, p<0.001). PCA of plasma proteins de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…CRP acts as an opsonin, supporting the ingestion of apoptotic cells by human macrophages, and plays a role in the clearance of apoptotic cells, especially during acute-phase reactions (18,19). Our data are consistent with other studies that also detected a high level of CRP in BALF during the fungal infections (20,21).…”
Section: Discussionsupporting
confidence: 83%
“…CRP acts as an opsonin, supporting the ingestion of apoptotic cells by human macrophages, and plays a role in the clearance of apoptotic cells, especially during acute-phase reactions (18,19). Our data are consistent with other studies that also detected a high level of CRP in BALF during the fungal infections (20,21).…”
Section: Discussionsupporting
confidence: 83%
“…42 In addition, a recent study showed that computed tomographic pulmonary angiography is a promising tool for detecting vessel interruption in cases of angioinvasion associated with IMIs. 43 Finally, our data challenge the notion, derived mainly from studies of monomicrobial infections in murine models, 44, 45 on whether single-pathogen molecular “signatures” or serum cytokine profile 46 would be diagnostically useful in real life, at least in heavily immunocompromised patients with hematological malignancies.…”
Section: Discussionmentioning
confidence: 63%
“…It can assess associations and interactions simultaneously13. The RF has been applied to many biological studies, such as gene expression14, metabolomics15, proteomics16, and GWA17. These studies showed that the RF method provides good accuracy, less internal examination of error, and high variable importance from mass biological data.…”
mentioning
confidence: 99%